2014
DOI: 10.1002/ps.3760
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference of NADPH-cytochrome P450 reductase of the rice brown planthopper,Nilaparvata lugens,increases susceptibility to insecticides

Abstract: The results provide first evidence that NlCPR contributes to the susceptibility to beta-cypermethrin and imidacloprid in N. lugens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 48 publications
7
48
1
1
Order By: Relevance
“…Alternatively, once key genes endowing metabolic resistance are identified, specific double-stranded RNAs can be designed and delivered to plants to accurately silence or suppress the gene(s) conferring resistance. For example, silencing of P450 or other metabolic genes in insects by RNA interference (RNAi) has been shown to increase insect susceptibility to insecticides or inhibitory plant metabolites (Mao et al, 2007;Liu et al, 2014). RNAi can simultaneously target several genes; therefore, it is especially suitable for studying (and likely combating) metabolic herbicide resistance, as this is often under polygenic control .…”
Section: Can Metabolic Herbicide Cross-resistance Be Mitigated?mentioning
confidence: 99%
“…Alternatively, once key genes endowing metabolic resistance are identified, specific double-stranded RNAs can be designed and delivered to plants to accurately silence or suppress the gene(s) conferring resistance. For example, silencing of P450 or other metabolic genes in insects by RNA interference (RNAi) has been shown to increase insect susceptibility to insecticides or inhibitory plant metabolites (Mao et al, 2007;Liu et al, 2014). RNAi can simultaneously target several genes; therefore, it is especially suitable for studying (and likely combating) metabolic herbicide resistance, as this is often under polygenic control .…”
Section: Can Metabolic Herbicide Cross-resistance Be Mitigated?mentioning
confidence: 99%
“…The hemimetabolous brown planthopper Nilaparvata lugens Stål (Hemiptera: Delphacidae) is one of the most destructive insect pests of rice that causes significant yield losses36. RNA interference (RNAi), which is a robust and powerful experimental tool, has been widely used to study gene functions through gene silencing34 in various piercing-sucking insects, including rice planthoppers3638394041. It has been reported that TRE regulates the expression of CHS in the cuticle and midgut of planthoppers, and the inhibition of chitin synthesis by suppressing or knocking down TRE leads to abnormal moulting and mortality.…”
mentioning
confidence: 99%
“…Originally, insecticide control was an important and very convenient way to control and decrease pest populations, but its improper use has led to pest resurgence and resistance, and to the accumulation of chemical residues (Xi et al 2014). In N. lugens , gene-function studies have also shown that RNAi of target genes could be used a pest-control strategy (Wang et al 2012, 2015; Xi et al 2014, 2015a,b; Liu et al 2015; Zhao et al 2016; Yang et al 2017). …”
mentioning
confidence: 99%